The origin of uniaxial negative thermal expansion in layered perovskites. (December 2017) - Ablitt, Chris; Craddock, Sarah; Senn, Mark; Mostofi, Arash; Bristowe, Nicholas
Abstract Why is it that ABO3 perovskites generally do not exhibit negative thermal expansion (NTE) over a wide temperature range, whereas layered perovskites of the same chemical family often do? It is generally accepted that there are two key ingredients that determine the extent of NTE: the presence of soft phonon modes that drive contraction (have negative Grüneisen parameters); and anisotropic elastic compliance that predisposes the material to the deformations required for NTE along a specific axis. This difference in thermal expansion properties is surprising since both ABO3 and layered perovskites often possess these ingredients in equal measure in their high-symmetry phases. Using first principles calculations and symmetry analysis, we show that in layered perovskites there is a significant enhancement of elastic anisotropy due to symmetry breaking that results from the combined effect of layering and condensed rotations of oxygen octahedra. This feature, unique to layered perovskites of certain symmetry, is what allows uniaxial NTE to persist over a large temperature range. This fundamental insight means that symmetry and the elastic tensor can be used as descriptors in high-throughput screening and to direct materials design. Negative thermal expansion: symmetry controls the behavior of perovskites Symmetry breaking is a major cause of uniaxial negative thermal expansion (NTE) in layered perovskites. Researchers at Imperial College, the University of Warwick and the University of Kent have discovered the atomic factors causing perovskite oxides, materials with the general formula ABO3, to show very different thermal expansion properties from their layered counterparts, known as Ruddlesden-Popper oxides. Using first-principles calculations, the researchers found that in layered perovskites certain structural motifs can deviate from a perfectly symmetric arrangement, whereas in regular perovskites they are more firmly fixed. This feature, prevalent in layered perovskites, is what allows uniaxial negative thermal expansion, i.e., the contraction of the material with increased temperature, to persist over a large temperature range. This fundamental insight could aid high-throughput screening for new NTE materials and help direct future materials design.